Estimation of Greenhouse Gas (GHG) emissions in waste management in Pekanbaru City, Indonesia - Hilal, Zia Ru`ya; Kristanto, Gabriel Andari; Dahlan, Astryd Viandila (Indonesian Journal of Multidisciplinary Science, 2025)
Municipal waste production in Indonesia is rapidly increasing due to population growth and economic development, contributing significantly to greenhouse gas (GHG) emissions. This research aims to develop effective waste management scenarios for Pekanbaru City, focusing on reducing GHG emissions through integrated treatment methods. Employing a comprehensive methodology, the study estimates GHG emissions from various waste management practices, including biological, thermal, and mixed methods. The research utilizes a basic model to calculate emissions based on activity data and emission factors, exploring current practices and innovative strategies like Black Soldier Fly (BSF) larvae for organic waste treatment. Findings reveal that the Mix scenario, which combines multiple waste management processes, results in the most significant reduction of GHG emissions, achieving a net emission of 112,985.89 tons of CO?-eq/year, compared to the existing scenario with 637,864.33 tons of CO?-eq/year. The study identifies key emission hotspots, emphasizing the need for improved management of organic waste through composting and recycling. The implications of this research highlight the importance of adopting integrated waste management strategies to mitigate GHG emissions effectively. The findings provide actionable insights for policymakers, promoting sustainable practices aligned with the 3R hierarchy (reduce, reuse, recycle) and supporting targeted interventions that can enhance environmental sustainability in urban settings.